2015
DOI: 10.1007/s00704-015-1544-5
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of topological pattern discovery and support vector machine in generating predictive models for Indian summer monsoon rainfall

Abstract: The present paper reports a study, where growing hierarchical self-organising map (GHSOM) has been applied to achieve a visual cluster analysis to the Indian rainfall dataset consisting of 142 years of Indian rainfall data so that the yearly rainfall can be segregated into small groups to visualise the pattern of clustering behaviour of yearly rainfall due to changes in monthly rainfall for each year. Also, through support vector machine (SVM), it has been observed that generation of clusters impacts positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Logistic regression was chosen and implemented on GIS system for quantitative prediction of rainfall and landslide in the study area [30]. SVM have been proved to impact positively the prediction of the Indian summer monsoon rainfall [31]. Also, hybrid models combining random forest (RF) and SVM have been used to predict amount of rainfall in rainfall occurring days [32].…”
Section: Learning: Rainfall Probability Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistic regression was chosen and implemented on GIS system for quantitative prediction of rainfall and landslide in the study area [30]. SVM have been proved to impact positively the prediction of the Indian summer monsoon rainfall [31]. Also, hybrid models combining random forest (RF) and SVM have been used to predict amount of rainfall in rainfall occurring days [32].…”
Section: Learning: Rainfall Probability Estimationmentioning
confidence: 99%
“…data. Support vector machines (SVM) [31] outperform logistic regression in binary classification, especially with growing training dataset [32]. When variables are mapped to higher dimensional space through divergent SVM kernels, nonlinear classification can be achieved by identifying maximum margin hyper plane between two sides [18,19].…”
Section: Estimated Ltr Probabilitymentioning
confidence: 99%
“…ANN outperformed established statistical benchmarks in 73% of the papers reviewed (Adya & Collopy, 1998). A recent study has revealed that about 12 different types of neural networks were used for Indian summer monsoon rainfall (ISMR) prediction since 2003 to 2014 and among these ANN accounts for 48% ISMR prediction approaches (Chattopadhyay & Chattopadhyay, 2016). The feed-forward neural network with backpropagation learning has been used for forecasting of ISMR.…”
Section: Introductionmentioning
confidence: 99%